COVID-19 Vaccination Refusal-Which Factors are Related in the Czech Republic, One of the Most Affected Countries in the World? - Zidkova, Radka; Malinakova, Klara; van Dijk, Jitse P; Tavel, Peter (International journal of public health, 2023)
Objective: This study examined the willingness to get vaccinated and the factors influencing this attitude in extreme settings-in the Czech Republic (at the time of the survey, the third-worst affected country in the world). Methods: We used national data from the general adult Czech population (N = 1,401) and measured attitudes towards vaccination, sociodemographic characteristics, government trust, knowledge about COVID-19 vaccines, personal characteristics, depression and anxiety. Results: Respondents who were more likely to refuse the vaccine were: female, younger, living without a partner, self-employed or unemployed, living in a town, believers outside the church, and did not trust the government, obtained information about the vaccine from social media, were extroverts and depressed. Conversely, respondents who were less likely to refuse the vaccine were: pensioners, people with higher education, respondents with better real knowledge about the COVID-19 vaccines, those who obtained information about the vaccine from an expert and those who had higher scores in neuroticism. Conclusion: This study thus offers a deeper understanding of the factors that might influence vaccine intention and subsequently the course of the COVID-19 pandemic.
Keywords: pandemie; dospělí; COVID-19; Humans; Czech Republic; vaccine refusal; Česká republika; úzkost; Adult; COVID-19 Vaccines; Anxiety; government trust; ženské pohlaví; vaccination; vakcíny proti COVID-19; lidé; Pandemics; Vaccination; knowledge; vakcinace; personal characteristic; Female